Effect of expanded glass particle size on compressive properties of vinyl ester syntactic foams. (27th January 2022) - Singh, Ashish Kumar; Behera, Rakesh; Shishkin, Andrei; Gupta, Nikhil
Abstract: The most common fillers for syntactic foam development are glass microballoons or fly ash cenospheres. However, the need for improved properties and reduced cost requires exploring other possibilities. In this work, syntactic foams of vinyl ester resin reinforced with expanded glass particles (EG) were fabricated and compressive properties of the composites were studied. The foam EGS was reinforced with smaller particles of size 0.04–0.125 mm in 15, 30, and 45 vol.% and EGL had larger particles of size 0.25–0.5 mm in 15 and 30 vol.%. Compression testing reveals that 45 vol.% smaller particles enhance the modulus of the EGS foam by up to 48% with a 3.4% reduction in yield strength compared to neat resin. Strain rate sensitivity was observed in both the modulus and yield strength values for all composites. Composite EGS with 15 and 30 vol.% filler showed better strength and modulus than the neat resin at 0.01 s −1 strain rate, which is an overall improvement in the material. When compared with the literature data, the foams made in the present work have the highest compressive strength and modulus for the same density.